Juridical Analysis in The Case of The Crime of Theft with Aggravation Committed by Minors - Muhammad Yusuf Al Ghani (UM Purwokerto Press, 2023)
Law No. 11/2012 regulates the special treatment of children in conflict with the law, which is different from adult criminal offenders. A child according to Article 1 number 1 of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection is a person who is not yet 18 (eighteen) years old, including children who are still in the womb.Children are vulnerable groups in society who need protection. This research aims at the qualification of criminal acts of theft with aggravation committed by children in the view of criminal law and knowing the basis of the judge's consideration in imposing punishment with aggravation committed by children.applied in order to answer the problem of criminal acts of theft with aggravation committed by children in the view of criminal law. The type of research used in this research is normative juridical by focusing on positive law and through a statutory approach. the results of this study know the basis of the judge's consideration in deciding a case of theft committed by a child and the judge's consideration is in accordance with the applicable provisions in the criminal code (KUHP).